Fraudulent Financial Reporting in Indonesia: Understanding the Causes and Crafting Solutions through Research - Dewa Ayu Kd Audya Sahya Devanie; Ida Iswara Purwani; Premananda, Uttari (Samā Jiva Jnānam (International Journal of Social Studies), 2024)
Financial fraud remains one of the most pervasive challenges in the corporate world, undermining the credibility of financial statements and eroding trust among investors, regulators, and the general public. This study aims to bridge the gap between global anti-fraud strategies and their applicability in Indonesia by providing a comprehensive analysis of the causes and potential solutions for fraudulent financial reporting in Indonesia. The study adopts a literature review approach to synthesize findings across selected literature. The findings highlight systemic issues such as structural and procedural factors such as weak internal controls, lack of regulatory enforcement, and cultural dynamics that discourage whistleblowing, making it an ideal backdrop for examining fraudulent financial reports in Indonesia. Despite significant strides made in improving corporate governance in Indonesia, enforcement remains a pressing challenge in combating financial fraud. Technological advancements, particularly in artificial intelligence (AI) and blockchain technology, offer promising solutions for addressing fraudulent behaviour.